Large subglacial meltwater features in the central Barents Sea - Bjarnadóttir, Lilja Rún; Winsborrow, Monica; Andreassen, Karin (Geology, 2017)
Source at https://doi.org/10.1130/G38195.1 . During the last glacial period large parts of the Arctic, including the Barents Sea, north of Norway and Russia, were covered by ice sheets. Despite several studies indicating that melting occurred beneath much of the Barents Sea ice sheet, very few meltwater-related landforms have been identified. We document ∼200 seafloor valleys in the central Barents Sea and interpret them to be tunnel valleys formed by meltwater erosion beneath an ice sheet. This is the first account of widespread networks of tunnel valleys in the Barents Sea, and confirms previous predictions that large parts of the ice sheet were warm based. The tunnel valleys are interpreted to be formed through a combination of steady-state drainage and outburst floods close to the ice margin, as a result of increased melting within a period of rapid climate warming during late deglaciation. This is the first study documenting widespread tunnel valley formation at the northern reaches of a Northern Hemisphere paleo–ice sheet, during advanced deglaciation and beneath a much reduced ice sheet. This indicates that suitable conditions for tunnel valley formation may have occurred more widely than previously reported, and emphasizes the need to properly incorporate hydrological processes in current efforts to model ice sheet response to climate warming. This study provides valuable empirical data, to which modeling results can be compared.